Pengaruh Media Video YouTube “Lapor Pak” terhadap Keterampilan Menulis Teks Anekdot pada Siswa Kelas X SMAN 6 Kediri Tahun Pelajaran 2023/20244 - Indria Rani, Evika; Pitoyo, Andri; Puspitoningrum, Encil (Universitas Nusantara PGRI Kediri, 2024)
Writing skills are productive skills and are considered as skills that require more attention than other skills. In learning Indonesian, one of the texts that must be studied by high school students is anecdotal texts. An anecdote text is a story that aims to convey criticism or satire through jokes. In learning anecdotal text, the YouTube video